THE ADMINISTRATION OF THE GOVERNMENT OF PEKANBARU CITY FIXED ASSET: THE MIX METHOD APPROACH - julian julian; vince ratnawati; yesi mutia basri (Jurnal Ilmiah Ekonomi Dan Bisnis, 2020)
This research has a formulation of problems, namely whether the administration of fixed assets in The Government of Pekanbaru City is already run by Permendagri number 19 the year 2016 about the guidelines of regional goods management, and any constraints in the fixed asset administration in the Government of Pekanbaru City. Samples on research with quantitative research methods are 10 OPD that have the largest fixed asset value on audited fiscal year balance 2017. For the method of qualitative research, informants or the speakers in this research are Head of Sub Division of Inventory and Elimination of Assets and Head of Sub Division Development and Evaluation of Regional Financial and Asset Management Agency (BPKAD) Pekanbaru City and Head of General and Personnel Subdivision alongside with Goods Manager in the Department of Education, Department of Public Works and Spatial Planning and Department of Public Housing and Settlement Areas. The method used in the study is a mixed research method with sequential explanatory research design. As for the quantitative method, used quantitative descriptive analysis. While the qualitative method, using the triangulation technique. This research indicates that The Government of Pekanbaru City is implementing fixed asset administration, with details of evaluation of bookkeeping, inventory, and reporting of fixed assets as well as results of the evaluation of document filling completeness, under Permendagri number 19 the year 2016 about the guidelines of regional goods management and The Government of Pekanbaru City faced obstacles in the administration of fixed assets, among others, supporting documents of insufficient fixed assets, the frequent goods manager change/mutation, the migration aspect of SIMDA BMD to SIPKD Asset as an asset management information system, and the lack of fixed asset management regulatory device policy.